Hubungan Asupan Energi, Pengetahuan Gizi dan Aktivitas Fisik dengan Kejadian Overweight pada Anggota Polisi di Polsek Tampan Pekanbaru Tahun 2017 - Novita Rany; Sinta Yuni Putri; Nurlisis Nurlisis (Jurnal Kesehatan Komunitas, 2018)
Overweight is an abnormal or excessive fat accumulation that is likely to cause various illnesses and adverse effects on a person. Overweight is the 5th leading cause of death in the world. Overweight can be an individual health problem of different jobs, including police officers, who are responsible for public safety. This study aimed to determine the relationship between energy intake, nutritional knowledge, physical activity and the incidence of overweight in Police officers in Tampan Police Department, Pekanbaru, in 2017. The design was cross sectional study. The population were police officers in Tampan Police Department, Pekanbaru, in 2017 which amounted to 98 policemen. The samples were 74 policemen. Data analysis used univariate and bivariate anlysis with chi-square test. The result showed that there were significant relationship of energy intake, nutrition knowledge, physical activity, and the incidence of overweight in police officers (p value < 0.05). Tampan Police Department should consider activities related to physical activity and conduct regularly nutrition consultation